Transcriptome of the GSH-Depleted Lens Reveals Changes in Detoxification and EMT Signaling Genes, Transport Systems, and Lipid Homeostasis - Whitson, Jeremy A. (Invest Ophthalmol Vis Sci, 2017)
PURPOSE: To understand the effects of glutathione (GSH)-deficiency on genetic processes that regulate lens homeostasis and prevent cataractogenesis. METHODS: The transcriptome of lens epithelia and fiber cells was obtained from C57BL/6 LEGSKO (lens GSH-synthesis knockout) and buthionine sulfoximine (BSO)-treated LEGSKO mice and compared to C57BL/6 wild-type mice using RNA-Seq. Transcriptomic data were confirmed by qPCR and Western blot/ELISA on a subset of genes. RESULTS: RNA-Seq results were in excellent agreement with qPCR (correlation coefficients 0.87–0.94 and P < 5E-6 for a subset of 36 mRNAs). Of 24,415 transcripts mapped to the mouse genome, 441 genes showed significantly modulated expression. Pathway analysis indicated major changes in epithelial-mesenchymal transition (EMT) signaling, visual cycle, small molecule biochemistry, and lipid metabolism. GSH-deficient lenses showed upregulation of detoxification genes, including Aldh1a1, Aldh3a1 (aldehyde dehydrogenases), Mt1, Mt2 (metallothioneins), Ces1g (carboxylesterase), and Slc14a1 (urea transporter UT-B). Genes in canonical EMT pathways, including Wnt10a, showed upregulation in lens epithelia samples. Severely GSH-deficient lens epithelia showed downregulation of vision-related genes (including crystallins). The BSO-treated LEGSKO lens epithelia transcriptome has significant correlation (r = 0.63, P < 0.005) to that of lens epithelia undergoing EMT. Protein expression data correlated with transcriptomic data and confirmed EMT signaling activation. CONCLUSIONS: These results show that GSH-deficiency in the lens leads to expression of detoxifying genes and activation of EMT signaling, in addition to changes in transport systems and lipid homeostasis. These data provide insight into the adaptation and consequences of GSH-deficiency in the lens and suggest that GSH plays an important role in lenticular EMT pathology.